Darwin, dharma, and the divine: evolutionary theory and religion in modern Japan - Godart, G. Clinton (Studies of the Weatherhead East Asian Institute, Columbia University, 2017)
The religious transmission of evolutionary theory in Meiji-era Japan -- Evolution, individuals, and the kokutai -- The dharma after Darwin : Meiji Buddhism and the embrace of evolution -- The promise of utopia : socialist Darwinism and evolutionary utopianism -- "Evolutionary theory is the superstition of modernity" -- Kannon's enduring embrace